Pemodelan Struktur Bawah Permukaan Menggunakan Data Magnetik di Area Tumpang Pitu Banyuwangi - Distiyo Wicaksono (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
This study aims to model the subsurface structure and identify potential mineralization in the Tumpang Pitu area, Sumberagung Village, Pesanggaran Subdistrict, Banyuwangi Regency. Geologically, this area is known to have a porphyry–epithermal system rich in mining commodities. The data used consists of regional secondary magnetic data obtained from the World Digital Magnetic Anomaly Map (WDMAM) with a spatial resolution of approximately 5 km. Spatial data processing was performed using Oasis Montaj software through the following steps: correction to the International Geomagnetic Reference Field (IGRF), coordinate conversion to UTM, Reduction to the Pole (RTP) with an inclination value of +34° and a declination of +0.5°, and separation of regional and residual anomalies using the Upward Continuation method at an altitude of 1,000 meters. The results of the reduction to the poles show that the total magnetic anomaly values range from -405.5 nT to +34.6 nT. Two-dimensional (2D) subsurface modeling was performed on two cross-sections (AB and CD) using the forward modeling method in Mag2DC software. Based on the results of iterative modeling, variations in magnetic susceptibility values were obtained, representing the subsurface geological response. The basement rock (old diorite) has the highest magnetic susceptibility value of 0,0284 SI, followed by coarse-grained tonalite intrusions (0,0083 SI) and fine-grained tonalite (0,0030 SI), which act as sources of hydrothermal fluids carrying Cu-Au-Mo mineralization. Meanwhile, the target zones consisting of hydrothermal breccia and strong alteration complexes are characterized by very low susceptibility values (0,0001 SI) due to the destruction of magnetic minerals by hydrothermal fluids. The upper layer is controlled by diatreme breccia (0,0005 SI), sedimentary/volcaniclastic (0,0012 –0,0020 SI), and overlain by andesite (0,0058 SI). This model successfully depicts the complete integration of the Tumpang Pitu porphyry-epithermal system, consistent with regional geological controls.
Finalisasi 16 Juli 2026_Yudi
Keywords: Forward modeling; Magnetic Anomalies; Oasis montaj; Susceptibility